HIV- 1 lentivirus tethering to the genome is associated with transcription factor binding sites found in genes that favour virus survival - Suleman, Saqlain; Payne, Annette; Bowden, Johnathan; Haque, Sharmin Al; Zahn, Marco; Fawaz, Serena; Khalifa, Mohammad S.; Jobling, Susan; Hay, David; Franco, Matteo; Fronza, Raffaele; Wang, Wei; et al. (Gene therapy, 2022)
Lentiviral vectors (LV) are attractive for permanent and effective gene therapy. However, integration into the host genome can cause insertional mutagenesis highlighting the importance of understanding of LV integration. Insertion site (IS) tethering is believed to involve cellular proteins such as PSIP1/LEDGF/p75, which binds to the virus pre-integration complexes (PICs) helping to target the virus genome. Transcription factors (TF) that bind both the vector LTR and host genome are also suspected influential to this. To determine the role of TF in the tethering process, we mapped predicted transcription factor binding sites (pTFBS) near to IS chosen by HIV-1 LV using a narrow 20 bp window in infected human induced pluripotent stem cells (iPSCs) and their hepatocyte-like cell (HLC) derivatives. We then aligned the pTFBS with these sequences found in the LTRs of native and self-inactivated LTRs. We found significant enrichment of these sequences for pTFBS essential to HIV-1 life cycle and virus survival. These same sites also appear in HIV-1 patient IS and in mice infected with HIV-1 based LV. This in silco data analysis suggests pTFBS present in the virus LTR and IS sites selected by HIV-1 LV are important to virus survival and propagation.
Gesehen am 21.04.2023